Retrospective Observations on the Ability to Diagnose and Manage Patients with Asthma through the Use of Impulse Oscillometry: Comparison with Spirometry and Overview of the Literature. (9th February 2014) - Saadeh, Constantine; Cross, Blake; Saadeh, Charles; Gaylor, Michael
Abstract : Objective . Impulse oscillometry (IOS) is an evolving technology for the diagnosis and followup of patients with asthma. Our objective is to review the findings on patients who underwent both spirometry and IOS during clinical evaluations of their asthma. The goal was to retrospectively evaluate IOS during the initial diagnosis and followup of patients with asthma in comparison with spirometry. Methods . We routinely perform IOS and spirometry evaluation in patients with suspected asthma during baseline visits and at followup. We reviewed the data on 39 patients over the age of 13 with asthma at baseline and following treatment with inhaled corticosteroids. IOS and spirometry were both done at baseline, following short acting bronchodilator administration, and at followup after at least three months of inhaled corticosteroid treatment. Results . IOS showed improvement in airway function both initially, following short acting bronchodilator introduction, and later after initiation of long term inhaled corticosteroid treatment, even when the spirometry did not reveal improvement. We noted the IOS improvement in the reactance or AX as well as the resistance in smaller airways or R5. Conclusion . IOS may provide a useful measure towards identifying an asthma diagnosis and followup without inducing the extra respiratory effort spirometry requires.